Gamma spectrum and coincidence summation simulations with Geant4 in the analysis of radionuclide using BEGe detector. (July 2018) - Liu, Chuanlei; Zhang, Weihua; Pierce, Dylan; Ungar, Kurt; Tulk, Christopher; Bean, Marc
Abstract: A Geant4 application has been developed to simulate the gamma spectrum of a BEGe detector. The summation effects were encompassed for both random and true coincidences through a time-based approach. The application well reproduces the typical spectral features such as full energy peaks, escape peaks, summation peaks and Compton/backscatter continuum. The simulated gamma response is consistent with empirical data within 3%, while simulations of the X-ray and baseline regions are valid within a 10% deviation. Abstract : Highlights: A time-based approach has been developed with Geant4 to simulate the summation effects. The typical gamma spectral features were well reproduced in the Geant4 application. The application can predict gamma response within 3% accuracy, while 10% for the remaining spectral regions.